2018
DOI: 10.4314/jfas.v9i6s.14
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the relevancy of sustainable building design to commercial property depreciation

Abstract: This preliminary study aims to explore the relationship between sustainable building design paradigms and commercial property depreciation, to assist in the understanding of sustainable building design impact towards commercial building value and rental de employs the qualitative method and analyses and depreciation issues in Malaysia. The findings present evidence that the eleven factors of sustainable building design paradigms are relevant to commercial property depreciation and obsolescence as agreed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…According to an investigation conducted by Wan Rodi [16], the main factors of green building attributes relevant to rental depreciation consist of green building status, materials, sustainable design configuration, sustainable site and soil characteristics, rooftop and on-site greenery, building management system, HVAC system, lighting system, water conservation system, indoor environmental monitoring system, and on-site renewable energy system. In Malaysia, the Green Building Index (GBI) has developed a very strong framework for green building certification for buildings.…”
Section: Attributes Of Green Buildings Affecting Rental Depreciationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to an investigation conducted by Wan Rodi [16], the main factors of green building attributes relevant to rental depreciation consist of green building status, materials, sustainable design configuration, sustainable site and soil characteristics, rooftop and on-site greenery, building management system, HVAC system, lighting system, water conservation system, indoor environmental monitoring system, and on-site renewable energy system. In Malaysia, the Green Building Index (GBI) has developed a very strong framework for green building certification for buildings.…”
Section: Attributes Of Green Buildings Affecting Rental Depreciationmentioning
confidence: 99%
“…Regarding the real estate market in Kuala Lumpur, Malaysia, the KL structure plan 2020 highlighted the significant number of older office buildings experiencing technological obsolescence. As green buildings become mainstream in the office market, the conventional older office buildings may depreciate faster and be less desirable [16,17]. New environmental attributes may impact the system's inbuilt environment, triggering obsolescence that has yet to be realized [18].…”
Section: Introductionmentioning
confidence: 99%
“…[10] examined mainly conflicting recommendations from the practitioner literature about the proper adjustment for deferred taxes and claimed that incentive alignment for owner and manager can be achieved by correct depreciation schedule of property. [11] has published a study which has successfully identified and analysed the relevant sustainable design factors that most likely contributes to the commercial property depreciation and obsolescence.…”
Section: Introductionmentioning
confidence: 99%